Efektivitas Layanan Bimbingan Kelompok Dengan Teknik Sosiodrama Untuk Meningkatkan Rasa Empati Peserta Didik Kelas VIII SMP Negeri 16 Kupang - Atamau, Yuventus M; Indrawan, Putu Agus; Masi, Lolang Maria (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
This research aims to determine the description of the group guidance process using sociodrama techniques, empathy and the extent of the effectiveness of group guidance using sociodrama techniques to increase the sense of empathy of class VIII students at SMP Negeri 16 Kupang. This research uses a quantitative approach with a pre-experimental research type with a one group pre test and post test research design. This research was carried out at SMP Negeri 16 Kupang. The sampling technique used is the purposive sampling method, namely the sample is taken according to the aims and objectives of the research, where a pre-test will be given to the entire population of 180 students, from the results of the pre-test students who show low empathy will be used as a sample, namely 10 students. The data collection technique uses an empathy and observation scale. The data analysis technique used is descriptive analysis, Mann Whitney hypothesis testing with the help of the SPSS For Windows 25Version program. The results of this research show that there is an increase in students' sense of empathy after being provided with group guidance services using sociodrama techniques. This is proven by the difference in the mean score before being given treatment, 5.50 and the mean score after being given treatment, 15.50. Apart from that, the Asymp value is obtained. Sig. (2-tailed) in the Mann Whitney hypothesis test is 0.000 < 0.05, which means Ha is accepted and H0 is rejected. Thus, it shows that group guidance services using sociodrama techniques can increase the sense of empathy of class VIII students at SMP Negeri 16 Kupang.